Clinical course of epithelial ovarian cancer patients with pleural effusion in Siriraj Hospital - Panupong Punthmatharith; Suwanit Therasakvichya (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective To evaluate the clinical course and determine the survival of epithelial ovarian cancer patients with pleural effusion. Study design Retrospective study. Materials and methods Data from epithelial ovarian cancer patients who had pleural effusion were reviewed from medical records between January 1997 and December 2007 in Siriraj Hospital. Characteristics, clinical outcomes and survival analysis were reported. Results 95 cases of epithelial ovarian cancer patients who had pleural effusion with medical records were identified. The median age was 53.7 years. There were 38.9% of these patients who had been proven as malignant pleural effusion. Only 23 cases (24.2%) underwent optimal cytoreductive surgery. Most patients received platinum-taxane combination chemotherapy. The median survival for malignant pleural effusion patients was 16.8 months, while median survival in the group who had negative cytological diagnose as malignant effusion was 31 months. The pleural effusions were subsided after the third and the sixth course of chemotherapy in 23% and 58% of cases respectively. Pleural intervention needed mostly in the first course of chemotherapy to release patients' symptom. Conclusion In epithelial ovarian cancer patients with malignant pleural effusion had poor survival. Platinum base-chemotherapy can reduce the clinical symptom in more than half of pleural effusion patients with no need of surgical intervention.